Integración de IoT e inteligencia artificial en la educación en ingeniería: Una experiencia formativa hacia la industria 5.0 - Rodriguez Casavilca, Hipólito M. (2025)
The transition toward Industry 5.0 requires the adaptation of traditional educational models by integrating emerging technologies such as Artificial Intelligence (AI) and the Internet of Things (IoT) into engineering education. This article presents a formative experience based on the transformation of automation laboratories at the Universidad Nacional Mayor de San Marcos, aimed at enhancing students’ technical and critical competencies to meet the challenges of Industry 5.0. An applied research methodology was implemented using an educational case study approach, leveraging simulation platforms, collaborative projects, and curricular alignment with international references such as the Springer Handbook of Automation. The quantitative and qualitative evaluation of a sample of 64 students revealed significant improvements: 88% achievement in cyber-physical competencies (integration of sensors, actuators, and controllers), approximately 85% in critical thinking (design and problem-solving), and over 90% in the application of intelligent technologies such as AI, IoT, and advanced simulation tools in real-world automation scenarios. The results validate the proposed methodological framework as a viable model for modernizing engineering education toward a more human-centered, sustainable, and intelligent vision.